An intelligent cryptographic key management model for secure communications in distributed industrial intelligent systems. Issue 12 (25th April 2021) - Chaeikar, Saman Shojae; Alizadeh, Mojtaba; Tadayon, Mohammad Hesam; Jolfaei, Alireza
Abstract: For secure communication in a distributed cooperation, generally, the data are encrypted and decrypted using a symmetric key. The process of creating, distributing, storing, deploying, and finally revoking the cryptographic keys is called key management. On the basis of the structure, usability, and complexity of the cyber‐physical systems, each one of the current key management practices is suitable for a specific range of applications. However, these schemes have some drawbacks in common, such as complicated key generation and distribution process, using key storage, attacks, and traffic load. This paper proposes a key management model for establishing secure communications in the distributed industrial intelligent systems. The model is attack resistant, has high usability in real‐world applications, and transforms the current customary key management workflow to enhance security and reduce weaknesses. Its main features include reduced process, intelligent attack resistance, producing dynamic keys with no additional cost, and eliminating key storage and revocation calls.